Prognostic impact of carboxylesterase 2 in cholangiocarcinoma - Goeppert, Benjamin; Renner, Marcus; Singer, Stephan; Albrecht, Thomas; Mehrabi, Arianeb; Pathil-Warth, Anita; Springfeld, Christoph; Köhler, Bruno Christian; Rupp, Christian; Weiss, Karl Heinz; Schirmacher, Peter; Rössler, Stephanie (Scientific reports, 2019)
Carboxylesterase 2 (CES2) is instrumental for conversion of ester-containing prodrugs in cancer treatment. Novel treatment strategies are exceedingly needed for cholangiocarcinoma (CCA) patients. Here, we assessed CES2 expression by immunohistochemistry in a CCA cohort comprising 171 non-liver fluke associated, intrahepatic (n = 72) and extrahepatic (perihilar: n = 56; distal: n = 43) CCAs. Additionally, 80 samples of high-grade biliary intraepithelial neoplastic tissues and 158 corresponding samples of histological normal, non-neoplastic biliary tract tissues were included. CES2 expression was highest in non-neoplastic biliary tissue and significantly decreased in CCA. Patients showing any CES2 expression in tumor cells had a significantly better overall survival compared to negative cases (p = 0.008). This survival benefit was also maintained after stratification of CES2-positive cases, by comparing low, medium and high CES2 expression levels (p-trend = 0.0006). Evaluation of CCA subtypes showed the survival difference to be restricted to extrahepatic tumors. Correlation of CES2 expression with data of tumor-infiltrating immune cells showed that particularly CD8+ T cells were more frequently detected in CES2-positive CCAs. Furthermore, treatment of CCA cell lines with the prodrug Irinotecan reduced cell viability, increased cytotoxicity and modulated inflammatory gene expression. In conclusion, reduced CES2 expression is associated with poor outcome and low CD8+ T cell infiltration in CCA patients. Further clinical studies could show, whether CES2 expression may serve as a predictive marker in patients treated with prodrugs converted by CES2.
Gesehen am 23.04.2019